CT venography after knee replacement surgery: comparison of dual-energy CT-based monochromatic imaging and single-energy metal artifact reduction techniques on a 320-row CT scanner. (February 2017) - Kidoh, Masafumi; Utsunomiya, Daisuke; Oda, Seitaro; Nakaura, Takeshi; Funama, Yoshinori; Yuki, Hideaki; Hirata, Kenichiro; Hatemura, Masahiro; Namimoto, Tomohiro; Yamashita, Yasuyuki
Background: An optimal metal artifact reduction (MAR) technique is needed for a reliable and accurate image-based diagnosis. Purpose: Using a 320-row scanner, we compared the dual-energy computed tomography (CT)-based monochromatic and the single-energy metal artifact reduction (SEMAR) techniques for CT venography (CTV) to identify the better imaging method for diagnosing deep vein thrombosis (DVT) in patients who had undergone knee replacement surgery. Material and Methods: Twenty-three consecutive patients with suspected DVT after unilateral knee replacement surgery underwent dual-energy CT (135/80 kVp). Monochromatic images of 35–135 keV were generated; the monochromatic image with the best signal-to-noise ratio (SNR) of the popliteal vein near the metal prosthesis were selected. The projection data of 80 kVp were reconstructed using MAR algorithm. The mean SNR ON MAR and the best SNR ON monochromatic images were compared. Two radiologists evaluated visualization of the metal artifacts on a four-point scale where 1 = extensive artifacts, 2 = strong artifacts, 3 = mild artifacts, and 4 = minimal artifacts. Results: The mean SNR was significantly higher on the MAR than the monochromatic images (12.8 ± 4.7 versus 7.7 ± 5.1, P  < 0.01) and the visual scores were significantly higher for MAR than monochromatic images (2.6 ± 0.8 versus 1.3 ± 0.4, P  < 0.01). Conclusion: For CTV after knee replacement surgery, the MAR technique is superior to the monochromatic imaging technique.